Guidelines for postoperative care in gynecologic/oncology surgery: Enhanced Recovery After Surgery (ERAS®) Society recommendations — Part II - Nelson, G.; Altman, A.D.; Nick, A.; Meyer, L.A.; Ramirez, P.T.; Achtari, C.; Antrobus, J.; Huang, J.; Scott, M.; Wijk, L.; Acheson, N.; Ljungqvist, O.; et al. (Gynecologic oncology, 2016)
•We provide evidence supporting postoperative management of patients undergoing gynecologic/oncology surgery.•This guideline will help integrate knowledge into practice, align perioperative care, and encourage future investigations.